A food-grade continuous electrospun fiber of hordein/chitosan with water resistance. (October 2020) - Guan, Xiao; Li, Lv; Li, Sen; Liu, Jing; Huang, Kai
Abstract: Hordein electrospun ultra-thin fibers are unstable in an aqueous environment. Chitosan was added to improve their water resistance. With increasing chitosan concentration, the viscosity and conductivity of the biopolymer blends increased, and the surface tensions remained almost constant. The structure and morphology of composite biopolymer fiber membranes showed that the average fiber diameter varied with chitosan concentration. ATR-FTIR spectra showed that the C–H stretching band changed or disappeared with increased chitosan. X-ray diffraction showed that chitosan was distributed in hordein fibers without crystallites. Compared with the hordein nanofibers, thermogravimetric analysis and derivative thermogravimetry curves showed that hordein/chitosan electrospun fibers had slightly decreased thermal stability. In conclusion, a low chitosan content improved the water resistance and other properties of hordein fibers, without changing their morphology or structure. Graphical abstract: Image 1 Highlights: Improved utilization of barley co-products from industrial processing is important. Chitosan improved hordein nanofibers water resistance. Addition of chitosan did not change hordein nanofibers morphology and structure. Enhanced electrospun fibers could be a good candidate for food packaging.